The Implementation of Inclusive Education in Early Childhood Education: Challenges and Solutions - Sari, Liana Novita; Laely, Khusnul; Astuti, Febru Puji (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Inclusive education at the early childhood education level plays a crucial role in providing equitable learning opportunities for all children, including those with special needs. It is believed that implementing inclusive education from an early age supports optimal child development and fosters a welcoming and equitable learning environment. However, its implementation in the field still faces several challenges that require further study. This study aims to describe the implementation of inclusive education at early childhood education institutions. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. This research was conducted at childhood education institutions in Jurangombo Selatan Village, Magelang City. The results indicate that the implementation of inclusive education at the Early Childhood Education level has not been running optimally. Obstacles experienced by teachers include limited competent teaching staff, fatigue at work, lack of parental openness regarding child development, and less than optimal government support regarding public school facilities and teacher competency improvement. This study emphasizes the importance of collaboration between educational institutions, parents, and the government to improve the quality of inclusive education at the early childhood education level.